A new rare species of Oedipoda Latreille, 1829 (Orthoptera: Acrididae) from South Italy - Fontana, Paolo; Buzzetti, Filippo Maria; Massa, Bruno (Zootaxa, 2019)
Oedipoda cynthiae n. sp. (Orthoptera: Acrididae: Oedipodinae) is described from Apulia (South Italy). In the past, the same population here considered had been assigned to O. miniata and later to O. charpentieri. Morphological features, biogeographical considerations, and a preliminary molecular analysis confirm that this population must be assigned to a new species, which is described and illustrated here.